Microsurgical Treatment of Cranial Dural Arteriovenous Fistulas: A Case Series and Literature Review - Jakštas, Domantas; Silva, Carolina Santos; Silva, Pedro Alberto; Vilarinho, Antonio (Acta medica Lituanica, 2026)
Dural arteriovenous fistulas are pathological vascular malformations within the dura mater, characterized by abnormal connections between pial arteries and veins. These are rare lesions that can present with a variety of neurological symptoms, and, when ruptured, can result in a fatal hemorrhage. This disease can be managed by endovascular embolization, surgical resection, and stereotactic radiosurgery. Particularly with the advancement of endovascular techniques, surgery is less frequently used to treat these lesions. However, it remains a viable treatment option in certain cases. In this article, we present a series of 17 patients with dural arteriovenous fistulas treated at a single tertiary neurosurgical center. This study was conducted at São João University Hospital in Porto, Portugal. We retrospectively collected data from all patients who underwent microsurgical or endovascular treatment for dural arteriovenous fistulas between 2014 and 2023. We collected information regarding the patients’ sex, age, and radiological classification of the dAVF, also, the treatment modality chosen, dAVF obliteration rate and information about any complications that have resulted from the treatment. Endovascular treatment had been attempted in 5 patients (29.4%), resulting in partial embolization of the dural arteriovenous fistulas in 3 patients (17.6%). In 2 patients (11.8%), embolization was attempted but deemed technically unfeasible. The remaining cohort, comprising 12 patients (70.6%), underwent surgical intervention as the primary treatment modality. Overall, all of the patients presented in this cohort underwent surgical resection. The factors why patients underwent surgical resection as the primary treatment modality were: endovascular embolization was deemed technically unfeasible due to the location in the anterior cranial fossa, or due to the multidisciplinary decision to operate on these lesions. Lesions were also operated on in the presence of a hematoma that required an evacuation. Immediate postoperative angiography showed that 94.1% (n = 16) of the patients achieved complete exclusion of the lesion. At the time of the latest follow-up, a second DSA was performed, and 88.23% (n = 15) of the patients showed complete obliteration of the lesion. 41.17 % of the patients (n = 7) had resolution of their pre-operative symptoms. 58.8 % (n = 10) remained symptomatic after the surgical procedure. The cumulative surgical complication rate in this cohort was 23.6% (n = 4). In this article, we also provide a comprehensive review of the literature regarding the treatment modalities that are available to treat this complex condition. In conclusion, surgical treatment is nowadays less frequently used, but it still remains a viable option for the treatment of dural arteriovenous fistulas. Our patient cohort demonstrated that selective treatment of these rare and complex lesions surgically is associated with high obliteration rates and relatively low rates of complications. Surgical treatment can be considered a primary treatment option when dealing with ethmoidal-type dural arteriovenous fistulas or others located within the anterior cranial fossa, and the presence of a hematoma requiring urgent evacuation.
Keywords: dural AVF; surgical resection; endovascular embolization; case series; literature review